1995
DOI: 10.1002/jcp.1041640119
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase cα in the induction of carcinoembryonic antigen by transforming growth factor β

Abstract: Previous studies showed that transforming growth factor beta 1 (TGF beta 1) regulates the expression of carcinoembryonic antigen (CEA) and CEA-cross-reactive glycoproteins (CEA-GLYs) in human colon carcinoma cells through a signal-transducing pathway associated with protein kinase C (PKC) (Chakrabarty, J. Cell. Physiol., 1992, 152:494-499). In this study we determined the role of the PKC alpha isoform in the regulation of CEA and CEA-GLYs expression by TGF beta 1. Expression of PKC alpha antisense RNA, through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…However, some studies have reported a relation between TGF-␤1 and CEA. [27][28][29] Our results revealed a significant correlation between serum levels of TGF-␤1 and serum levels of CEA. Serum TGF-␤1 increased with increasing serum levels of CEA.…”
Section: -12mentioning
confidence: 70%
“…However, some studies have reported a relation between TGF-␤1 and CEA. [27][28][29] Our results revealed a significant correlation between serum levels of TGF-␤1 and serum levels of CEA. Serum TGF-␤1 increased with increasing serum levels of CEA.…”
Section: -12mentioning
confidence: 70%
“…Protein kinase C (PKC) is a ubiquitous family of protein kinases that is involved in transmembrane signaling in cellular responses to extracellular signals (Nishizuka, 1992). We have previously shown that in Moser cells TGFP rapidly stimulates a PKC phosphotransferase activity before the stimulation of the adhesion response and that the stimulation of PKC phosphotransferase activity by TGFP is required for the adhesion response to occur (Chakrabarty, 1992b;Chakrabarty and Huang, 1995). In addition, the postreceptor TGFP-PKC signal pathway controls the adhesion but not the antiproliferative response to TGFP (Chakrabarty et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Increase in cell-matrix adhesion is mediated through the induction of the synthesis and secretion of the extracellular matrix (ECM)-adhesion molecules laminin and fibronectin with a concurrent upregulation of the expression of cell-surface integrin receptors for these ECM-adhesion molecules (Huang and Chakrabarty, 1994;Chakrabarty et al, 1998), collectively termed ECM remodeling). TGFb regulates ECM remodeling in the Moser cells in a protein kinase C-dependent manner (Chakrabarty and Huang, 1995;Chakrabarty et al, 1998). Almost concurrently with ECM remodeling, TGFb induces cell-cell adhesion through the induction of E-cadherin expression (Wang and Chakrabarty, 2001), an epithelial associated homotypic cell-cell adhesion molecule known to have tumorsuppressive function in colon cancer (Breen et al, 1995).…”
mentioning
confidence: 99%